Peripheral benzodiazepine receptor ligand Ro5-4864 inhibits isoprenaline-induced cardiac hypertrophy in rats - Jaiswal, Amardeep; Kumar, Santosh; Enjamoori, Rajesh; Seth, Sandeep; Dinda, Amit Kumar; Maulik, Subir Kumar (European journal of pharmacology, 2010)
Oxidative stress plays a significant role in the pathogenesis of cardiac hypertrophy. Peripheral benzodiazepine receptors are ubiquitously expressed in various tissues, including the heart. Peripheral benzodiazepine receptors have been reported to be involved in the protection of cells against oxygen radical damage. The present study was designed to determine whether Ro5-4864 (a peripheral benzodiazepine receptor ligand) can inhibit isoprenaline-induced cardiac hypertrophy. Male Wistar rats (body weight 150–200g) were administered, isoprenaline (5mg/kg, body weight, subcutaneously) alone or along with Ro5-4864 (0.1 and 0.5mg/kg, body weight, intraperitoneally) once daily for 14days. Control rats received normal saline subcutaneously (1.0ml/kg). Isoprenaline-induced changes in heart weight to body weight ratio, left ventricular wall thickness (M-mode echocardiography and gross morphometry) and myocyte size were significantly prevented by both the doses of Ro5-4864. Ro5-4864 also attenuated isoprenaline-induced increase in interstitial fibrosis, lipid peroxidation and changes in endogenous antioxidants (glutathione, superoxide dismutase and catalase). Isoprenaline-induced cardiac hypertrophy was associated with increased expression of β myosin heavy chain, which was also prevented by Ro5-4864. This is the first study to demonstrate a salutary effect of Ro5-4864 in experimental cardiac hypertrophy.